2005
DOI: 10.1016/j.chembiol.2004.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Specificity and Affinity of Natural Product Cyclopentapeptide Inhibitors against A. fumigatus, Human, and Bacterial Chitinases

Abstract: Family 18 chitinases play key roles in organisms ranging from bacteria to man. There is a need for specific, potent inhibitors to probe the function of these chitinases in different organisms. Such molecules could also provide leads for the development of chemotherapeuticals with fungicidal, insecticidal, or anti-inflammatory potential. Recently, two natural product peptides, argifin and argadin, have been characterized, which structurally mimic chitinase-chitooligosaccharide interactions and inhibit a bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
86
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(92 citation statements)
references
References 63 publications
(13 reference statements)
6
86
0
Order By: Relevance
“…Pentoxifylline competitively inhibits Family 18 glycosylhydrolases (endochitinases) by forming extensive stacking interactions with conserved tryptophan 70 mg/ml PX 0.6 6 0.6 a 140 mg/ml PX 2.5 6 2.5 a 280 mg/ml PX 4.9 6 1.2 a residues of the enzyme active site. The mode of inhibitory action of pentoxifylline mimics that of allosamidin on fungal, bacterial, and human chitinases (Rao et al 2005a(Rao et al , 2005b. Similar to the in vitro activity results, allosamidin and its analogue isoallosamidin were shown to significantly affect endo-chitinase activity, while having minimal to no effect on exo-chitinase activity in a Chironomus midge cell line (Spindler and Spindler-Barth 1994).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Pentoxifylline competitively inhibits Family 18 glycosylhydrolases (endochitinases) by forming extensive stacking interactions with conserved tryptophan 70 mg/ml PX 0.6 6 0.6 a 140 mg/ml PX 2.5 6 2.5 a 280 mg/ml PX 4.9 6 1.2 a residues of the enzyme active site. The mode of inhibitory action of pentoxifylline mimics that of allosamidin on fungal, bacterial, and human chitinases (Rao et al 2005a(Rao et al , 2005b. Similar to the in vitro activity results, allosamidin and its analogue isoallosamidin were shown to significantly affect endo-chitinase activity, while having minimal to no effect on exo-chitinase activity in a Chironomus midge cell line (Spindler and Spindler-Barth 1994).…”
Section: Discussionsupporting
confidence: 61%
“…In a worker subterranean termite hindgut alone, there are an estimated 350,000 bacterial cells (primarily Streptococcus, Bacteroides, and Enterbacteriacea species) and tens of thousands of individual protists (primarily Dinenympha, Pyrsonympha, and Trichonympha species), which are specialized to live in the anaerobic conditions of the termite hindgut (Lewis and Forschler 2010, Schultz and Breznak 1978, Yamaoka et al 1986). Pentoxifylline and other chitinase-inhibiting molecules are active against bacterial, protist, fungal, insect, crustacean, and human chitinases (Rao et al 2005a(Rao et al , 2005b. Lewis and Forschler (2010) reported significant impacts on protist populations within eastern subterranean termites fed diet containing one of five commercially used chitin synthesis-inhibiting insecticide active ingredients.…”
Section: Discussionmentioning
confidence: 99%
“…FTD-0668 and Clonostachys sp. FO-7314, respectively (19 -21), have IC 50 values in the nanomolar to micromolar range (21)(22)(23)(24)(25). Other molecules, such as chitobiose and chitotriose thiazolines (26), xanthine derivatives (27), and CI-4 (28, 29), exhibit nanomolar to millimolar level inhibitory activities.…”
Section: Glycoside Hydrolase Family 18 (Gh18)mentioning
confidence: 99%
“…FTD-0668), and was found to be a potent inhibitor of blowfly 6 and Serratia marcescens chitinases (SmChi). [9][10][11][12] Recently, argifin complexes with fungal (Aspergillus fumigatus), human and bacterial chitinases have been resolved by X-ray crystallography. 11,12 These studies revealed that there are at least four conserved hydrogenbond interactions between the N o -methylcarbamoyl-L-arginine moiety and the polar groups arrayed in the hydrolytic pocket of the family 18 chitinases examined to date.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] Recently, argifin complexes with fungal (Aspergillus fumigatus), human and bacterial chitinases have been resolved by X-ray crystallography. 11,12 These studies revealed that there are at least four conserved hydrogenbond interactions between the N o -methylcarbamoyl-L-arginine moiety and the polar groups arrayed in the hydrolytic pocket of the family 18 chitinases examined to date. The remarkable fidelity of the hydrogen-bonding network between the chitinases and the argifin ligand implicates its critical role in revealing the micro-to nanomolar range of inhibition.…”
Section: Introductionmentioning
confidence: 99%